Pola Interaksi Sosial Anggota Subak Hindu dan NonHindu di Subak Pemaket Awen Selatan Desa Pengambengan, Kecamatan Negara, Kabupaten Jembrana - ASTIAWAN, I WAYAN NIKA; DIARTA, I KETUT SURYA; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.2, April 2014, 2018)
Pattern Of Interaction Social In Members Of Hindu And Non Hindu In Subak Pemaket Awen Selatan Pengambengan Village Negara Subdistrict Jembrana Regency Subak is a customary law community that has socio-agrarian-religious-economic characteristics, Subakof Pemaket Awen Selatan is one of subaks in Bali which has members of Hindu and Non Hindu. Religious differences embraced by members of Subak Pamekat Awen Selatan have led to the potential for conflict. This study was located in Subak Pembaket Awen Selatan, Pengambengan Village, Sub-District of Negara, Jembrana District. The study was conducted from January to March 2017. The data collection used snowball sampling method, that is by determining the number of samples of each religion that consisted of 15 people. Method of analyzing data used descriptive qualitative method. The results showed that the pattern of interaction in Subakof Pembaket Awen Selatan is categorized into two, namely the associative patterns (cooperation, help, and accommodation) and dissociative patterns (contravenes and conflicts). The communication pattern in Subak Pembaket Awen Selatan was heterophilic that is, the communication that occurs between different beliefs and backgrounds. The interaction model explains the limits of values and beliefs shared by each religion. These limits are activities that may and should not be done when Hindu and non-Hindu members interact and perform the six tasks and functions of subak.